2021
DOI: 10.1080/23299460.2021.1955613
|View full text |Cite
|
Sign up to set email alerts
|

From Responsible Research and Innovation to responsibility by design

Abstract: Drawing on more than eight years working to implement Responsible Research and Innovation (RRI) in the Human Brain Project, a large EU-funded research project that brings together neuroscience, computing, social sciences, and the humanities, and one of the largest investments in RRI in one project, this article offers insights on RRI and explores its possible future. We focus on the question of how RRI can have long-lasting impact and persist beyond the time horizon of funded projects. For this purpose, we sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…Such a proactive attitude does not imply accountability but rather an expansion of the spheres of influence and interest of the scientist. Even if a mechanism could be devised to hold scientists accountable for broader safety issues, studies into the implementation of RRI have shown that legal requirements, much like the formalization of safety protocols, narrow the scope of attention and impede reflection, thinking about long-term consequences, and reaching out to stakeholders [ 47 ]. Such a strategy would thus effectively work contrary to the aims of SbD in directing attention to uncertain and unpredictable impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Such a proactive attitude does not imply accountability but rather an expansion of the spheres of influence and interest of the scientist. Even if a mechanism could be devised to hold scientists accountable for broader safety issues, studies into the implementation of RRI have shown that legal requirements, much like the formalization of safety protocols, narrow the scope of attention and impede reflection, thinking about long-term consequences, and reaching out to stakeholders [ 47 ]. Such a strategy would thus effectively work contrary to the aims of SbD in directing attention to uncertain and unpredictable impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we should bring ethical discussions more to the forefront, highlighting the social responsibility of psychological research, its public communication and the integrity of its products. Such ethical discussions are partly implemented within the approaches of “ELSI – Ethical, Legal and Social Issues of Research” (Lohse et al, 2020; Rehmann-Sutter, 2011) and “RRI – Responsible Research and Innovation” (Stahl et al, 2021). These approaches have been established in the last decade and have been promoted by some funding institutions, such as the European Union.…”
Section: Psychological Humanities In the Wake Of The Replication Crisismentioning
confidence: 99%
“…The ISO 56003 recommends debating the consequences and impacts of the research for all stakeholders [16], as mentioned in the introduction. In this context, the concept of Responsible Research and Innovation (RRI) emerges [29][30][31][32]. Thapa et al [7] mentioned that science and innovation have as their central objectives socioeconomic transformation and social development.…”
Section: Theoretical Backgroundmentioning
confidence: 99%